2002
DOI: 10.1017/s0007125000161884
|View full text |Cite
|
Sign up to set email alerts
|

Sexual molestation of males: Associations with psychological disturbance

Abstract: Sexual abuse as a child or adult is associated with later psychological problems. All forms of sexual molestation were predictive of deliberate self-harming behaviour in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…Elliott, Mok, and Briere (), whose sample consisted of homosexual and bisexual men, reported a victimisation rate of 3.8%, while Ratner et al () reported a much higher victimisation rate of 14%. Similarly, a high victimisation rate (18%) was reported by King, Coxell, and Mezey (), whose sample consisted of men attending genitourinary medicine clinics. However, many male victims of sexual offences do not report their victimisation to anyone, including support organisations (Davies, ), which suggests that figures cited in the literature are likely to vastly under‐estimate the true occurrence of male sexual victimisation.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Elliott, Mok, and Briere (), whose sample consisted of homosexual and bisexual men, reported a victimisation rate of 3.8%, while Ratner et al () reported a much higher victimisation rate of 14%. Similarly, a high victimisation rate (18%) was reported by King, Coxell, and Mezey (), whose sample consisted of men attending genitourinary medicine clinics. However, many male victims of sexual offences do not report their victimisation to anyone, including support organisations (Davies, ), which suggests that figures cited in the literature are likely to vastly under‐estimate the true occurrence of male sexual victimisation.…”
Section: Introductionmentioning
confidence: 54%
“…Research into the victim, offender and offence characteristics of male‐on‐male sexual assault could have an impact on reducing the myths that surround this offence, enabling victims to come forward and report the offence. This, in turn, could help generate an increase in the support available for male victims, both in terms of immediate as well as long‐term physical and psychological treatment (King et al, ). It could also increase recognition for victims among legal and medical professionals, enabling victims to be treated better and with more respect.…”
Section: Introductionmentioning
confidence: 99%
“…Further, male self‐cutters were not more likely than non‐cutters to have experienced childhood sexual abuse, unlike female self‐cutters. Male self‐cutters may show relatively low dissociation compared to female self‐cutters because fewer boys than girls fall victim to sexual abuse, while experiencing sexual molestation has been linked with self‐harming behavior 52 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current sample of 101 participants is large compared to many studies in the literature. This is especially true of studies that have utilized data collected from children (e.g., Mian, Marton, & LeBaron, 1996, who examined 70 female victims; Nelson, Moser, Johnson, Graves, & Hart, 1999, who examined 25 female victims; Young, Bergandi, & Titus, 1994, who examined 40 victims) as opposed to retrospective adult studies (e.g., King, Coxell, & Mezey, 2002, who studied 2,545 men).…”
Section: Discussionmentioning
confidence: 99%